1997
DOI: 10.1080/02652039709374569
|View full text |Cite
|
Sign up to set email alerts
|

Quick methods to control compliance of plastic materials with food packaging regulations

Abstract: A general strategy is presented, aiming to provide plastics manufacturers, food industries and enforcement laboratories with quick methods to check whether migration from materials for food contact will be acceptable during the time of use. The strategy involves several steps, with increasing time demand and cost. Monitoring extraction kinetics allows both the optimization of the extraction time, and the selection of conditions where extraction is more severe than migration. The influence of the extracting sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…It can be observed that there is not a reasonable agreement between overall migration values obtained with olive oil and those obtained with the different fatty food simulants. The closest results for PE/PA are obtained with 95% ethanol, a polar simulant, which could be more attractive for polar migrants, 3 although under thermal treatment 95% ethanol results in greater values on overall migration, which could be attributed to the fact that, on the basis of Hansen's parameters, olive oil presents a polarity that can be represent as (d p = 2; d H = 2), while ethanol presents higher values (d p = 4; d H = 9.5).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…It can be observed that there is not a reasonable agreement between overall migration values obtained with olive oil and those obtained with the different fatty food simulants. The closest results for PE/PA are obtained with 95% ethanol, a polar simulant, which could be more attractive for polar migrants, 3 although under thermal treatment 95% ethanol results in greater values on overall migration, which could be attributed to the fact that, on the basis of Hansen's parameters, olive oil presents a polarity that can be represent as (d p = 2; d H = 2), while ethanol presents higher values (d p = 4; d H = 9.5).…”
Section: Resultsmentioning
confidence: 72%
“…2 Temperature is probably the most important environmental variable affecting transport processes. Some authors [3][4][5] have studied the thermal effect on specific migration and under different temperature conditions, although little work has been reported on the suitability of alternative food simulants for migration testing at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of modern instruments is good and menu-driven software makes the technique more readily accessible to the general analyst. 'H-NMR requires quite expensive equipment, but the essential information can often be obtained in a very short time from the spectra (Castle et al 1992, Feigenbaum et al 1997, Metois et al 1998). This approach therefore efficiently complements methods previously developed and for these reasons NMR spectra are included in the additives handbook.…”
Section: Nmr Spectramentioning
confidence: 99%
“…The spectra can be used to identify additives either pure or as constituents of polymer extracts. It has been shown (Feigenbaum 1997) that 'H-NMR is a powerful tool for the quality control of some food packaging plastics, especially in an industrial framework. The materials are extracted by a suitable solvent and after evaporation to dryness the 'H-NMR spectrum of the extract is recorded.…”
Section: Nmr Spectramentioning
confidence: 99%
“…These models have been discussed elsewhere (Baner et al 1994, Piringer 1997a, b, Limm and Holli® eld 1996, Begley 1997, Feigenbaum et al 1997 and are based upon Fickian diOE usion principles. Recently a commercial software package has become available based upon the`Piringer model' (Piringer 1997b).…”
Section: Introductionmentioning
confidence: 99%